Immune activation, smoking, and vaccine response. (2nd January 2017) - Younas, Mehwish; Carrat, Fabrice; Desaint, Corinne; Launay, Odile; Corbeau, Pierre
Abstract : Here, we tested the hypothesis that chronic immune activation might fuel interindividual variability in vaccine response in the model of hepatitis B virus vaccine in HIV-1-infected adults. We observed that the marker of inflammation soluble tumour necrosis factor receptor I (sTNFRI) is predictive for vaccine efficiency. We also established that the link between tobacco smoking and impaired vaccine response might be mediated by inflammation. These data are a step forward in personalized vaccination.